"One‐pot" synthesis of well‐defined functional copolymer and its application as tumor‐targeting nanocarrier in drug delivery. Issue 12 (27th January 2014) - Wang, Chenhong; Qiao, Lei; Yan, Husheng; Liu, Keliang
ABSTRACT A one‐pot synthesis is developed for PEG600‐b‐poly(glycerol monoacrylate) (PEG600‐b‐PGA), by which folate and superparamagnetic iron oxide nanoparticles (SPIONs) are assembled to form folic acid‐conjugated magnetic nanoparticles (FA‐MNPs) as a tumor targeting system. The synthesis consists of a "click" reaction and atom transfer radical polymerization (ATRP) to obtain the well‐defined furan‐protected maleimido‐terminated PEG600‐b‐poly(solketal acrylate) (PEG600‐b‐PSA) copolymer. After deprotection, the key copolymer N‐maleimido‐terminated PEG600‐b‐PGA is successfully conjugated with thiol derivatives of folate and FITC, respectively. FA‐MNPs are developed by assembling of the resulting polymer FA‐PEG600‐b‐PGA with SPIONs, and characterized for their size, surface charge, and superparamagnetic properties. To investigate the cellular uptake of the nanoparticles by Hela cells and φ2 cells using fluoresce technique, FA‐FITC‐MNPs are also obtained by assembling of FA‐PEG600‐b‐PGA, FITC‐PEG600‐b‐PGA with SPIONs. Qualitative and quantitative determinations of FA‐FITC‐MNPs show that the particles specifically internalized to Hela cells. No significant cytotoxicity is observed for these two kinds of cell lines. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40405.